Differential matrix metalloproteinase expression in cases of multiple sclerosis and stroke. - Anthony, D; Ferguson, B; Matyzak, M; Miller, K; Esiri, M; Perry, V (1997)
Multiple sclerosis (MS) and stroke pathology are characterized blood-brain barrier breakdown, leucocyte emigration, and tissue destruction. Each process is thought to involve the matrix metalloproteinases (MMP), but little is known of their expression. We undertook to investigate whether MMP expression is dependent on the nature of the CNS lesion and whether expression would coincide with the histopathology. MS or cerebral-infarct tissue was examined for the presence of gelatinase-A, gelatinase-B, matrilysin and stromelysin-1. Gelatinases A and B and matrilysin expression was found to be up-regulated in microglia/macrophages within acute MS lesions. In active-chronic MS lesions, matrilysin and gelatinase-A expression was pronounced in the active borders. In chronic MS lesions, the expression of matrilysin was confined to macrophages within perivascular cuffs. The pattern of MMP expression in infarct lesions differed considerably. Gelatinase-B was strongly expressed by neutrophils in tissue from patients up to 1 week after an infarct, whereas gelatinase-A and matrilysin staining was much less marked. From 1 week to 5 years, neutrophils were absent and the large number of macrophages present were expressing matrilysin and gelatinase A. Only a low level of gelatinase-A and matrilysin expression was observed in normal brain controls. Thus, MMPs are expressed in inflammatory lesions in the CNS, but their individual expression is dependent on the nature and chronicity of the lesion. However, the general pattern of expression, in perivascular cuffs and in active lesions, supports a role for these enzymes as mediators of blood-brain barrier breakdown and tissue destruction, both in MS and in cerebral ischaemia.